LANGUAGE POLICY THE LIKELY SOLUTION FOR ZIMBABWEAN PROBLEMS - Mhute, Isaac (European Scientific Journal, ESJ, 2015)
Zimbabwe, just like the others in Africa, is a developing country whose distance away from becoming developed is not getting any shorter inspite of a whole lot of programmes that have been implemented to address the issue. This demonstrates a need for reorientation in as far as the perception of development and the methods of pursuing it are concerned. The paper argues for the need to revisit the country’s language policy and efforts towards the attainment of development in the light of how welldeveloped countries like China have got to where they are. It is a qualitative research-based paper that relied on observing Zimbabwean people in relation to their policies. It emerged that maladministration, high levels of corruption, high levels of deadly diseases like HIV/AIDS are examples of the major obstacles to development in Africa and these result mainly from the absence of unhuism or ubuntuism that is typical of a typical Zimbabwean community. This raises the need for the nation to understand the role of language, culture and tradition in development.